Committed - Krueger, Lisa.; Affleck, Casey; Goran Visnjic; Heather Graham; Luke Wilson (USA Miramax, 2000)
The plot of ""Committed"" is centered around the story of an intense young woman, played by Graham, whose husband leaves her in order to find himself. She then follows him cross-country and when she catches up with him, complications arise.
A young woman goes in search of her midlife crisis suffering husband who left her.
Lisa Krueger
Languages : English, Turkish Subtitle : Turkish
Keywords: Drama; Comedy